2011
DOI: 10.1093/infdis/jir433
|View full text |Cite
|
Sign up to set email alerts
|

Fine Epitope Specificity of Anti-erythropoietin Antibodies Reveals Molecular Mimicry With HIV-1 p17 Protein: A Pathogenetic Mechanism for HIV-1–Related Anemia

Abstract: These results suggest that the main body of anti-Epo is directed against a functional domain of Epo, and that the presence of anti-Epo can be considered to be a result of a molecular mimicry mechanism, which is caused by the similarity between the Ep1 region and the p17 protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…The molecular mimicry between HIV protein and self-antigen may explain these higher risks of incident SLE and autoimmune haemolytic anaemia in patients with HIV. The molecular mimicry between HIV viral protein and self-antigens could induce autoantibody production2 19 and might be associated with the development of autoimmune diseases 28…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular mimicry between HIV protein and self-antigen may explain these higher risks of incident SLE and autoimmune haemolytic anaemia in patients with HIV. The molecular mimicry between HIV viral protein and self-antigens could induce autoantibody production2 19 and might be associated with the development of autoimmune diseases 28…”
Section: Discussionmentioning
confidence: 99%
“…When HIV infects a host, it may induce production of autoantibodies due to the structural antigen similarity between viral proteins and self-antigens 2 3. The molecular mimicry between HIV protein and self-antigens could cause antibody cross-reactions and lead to development of autoimmune disease 4.…”
Section: Introductionmentioning
confidence: 99%
“…A recent report demonstrates that molecular mimicry between erythropoietin (EPO) and the HIV-1 p17 protein can lead to circulating auto-antibodies against endogenous EPO in some HIV ϩ patients, blunting the normal physiologic cytokine response to anemia. 18 Several studies have also demonstrated a direct effect of HIV on hematopoietic progenitor cells and EPO responsiveness. HIV-2 infection of BM progenitor cells in the in vitro setting has been shown previously to inhibit erythyropoiesis directly at the BFU-E and CFU-E stage of differentiation.…”
Section: Multifactorial Pathogenesis Of Anemia In Hivmentioning
confidence: 99%
“…[8] The mechanisms potentially involved in the production of AAbs in the context of HIV infection include molecular mimicry, [9,10] dysregulation of the interaction between B and T lymphocytes, [11] and polyclonal B lymphocyte activation. Studies investigating this latter hypothesis did not find a significant relationship between polyclonal hypergammaglobulinemia and the presence of ANAs, ANCAs, or aPL, but these studies were mostly performed in the pre-highly active antiretroviral therapy (HAART) era and patients’ immunovirological status was not always well described.…”
Section: Introductionmentioning
confidence: 99%